PENGARUH LOCUS OF CONTROL DAN PERILAKU PRO SOSIAL MAHASISWA UIN DATOKARAMA PALU - Saguni, Fatimah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2022)
This research aims to analyze the Locus of Control and Prosocial Behavior of UIN Datokarama Palu Students. To answer this main issue, the author uses quantitative methods and uses a Likert scale to look at symptoms or events that are understood through conscious experience of social locus of control and prosocial behavior of UIN Datokarama Palu students, while the data collection techniques used are observation and in-depth interviews, then The data analysis technique in this research is using the Miles and Huberman interactive model. The research results show that individuals who have a locus of control tend to have a high social spirit. This will enable him to develop various social activities